Pengaruh Penggunaan Sisik Ikan Bandeng Terhadap Kadar Kalsium, Daya Kembang dan Organoleptik Camilan Stick - Chairunnisa Nur Aulia Fajari; Muh Yusuf; nurrahman nurrahman (Jurnal Pangan dan Gizi, 2019)
Stick is snack which favoured by society but lack of nutrition content, especially mineral calcium, then needed an other materials to completed it with the addition of Chanos fish scales fluor. The general purposed of this research was to determined the effect of used Chanos fish scales to calcium levels, swell strength and organoleptic of stick snack. The method of this research is experiments methods used completely randomized design (RAL) monofaktorial by a factor variation of addition 0%, 1%, 2%, 3%, 4% and 5%. Statistical analysis showed an influence from the addition of fish scales fluor to calcium levels and organoleptic that showed from p value <0,05, but no influenced on the swell strength. The best treatment of this research are 3% additional of fish scales with calcium levels 0,38%, swell strength value 1,375%, quality scale value 3,675 and hedonic value 2,83. The conclution of this research are more higher percentage additional of Chanos fish scales will increase calcium level and hedonic value but degraded the quality scale value.